Long-Term Effects of Climate and Competition on Radial Growth, Recovery, and Resistance in Mongolian Pines - Sun, ShouJia; Zhang, JinSong; Zhou, Jia; Guan, ChongFan; Lei, Shuai; Meng, Ping; Yin, ChangJun (Frontiers in Plant Science, 2021)
Understanding the response of tree growth and drought vulnerability to climate and competition is critical for managing plantation forests. We analyzed the growth of Mongolian pines in six forests planted by the Three-North Shelter Forest Program with tree-ring data and stand structures. A retroactive reconstruction method was used to depict the growth-competition relationships of Mongolian pines during the growth period and their climatic responses under different competition levels. Drought vulnerability was analyzed by measuring the basal area increment (BAI) of different competition indices (CIs). In young trees, differences in BAIs in stands with different CIs were not statistically significant. After 15–20 years, medium- and high-CI stands had significantly lower tree-ring widths (TWs) and BAIs than the low-CI stands (p<0.05). The standardized precipitation evapotranspiration index (SPEI), precipitation, relative humidity, and vapor pressure deficit were major factors affecting tree growth. On a regional scale, climate outweighed competition in determining radial growth. The relative contribution of climatic factors increased with the gap in SPEI between plantation sites and the native range, while the reverse pattern of the competition-growth relationship was observed. Drought reduced TWs and BAIs at all sites. Stands of different CIs exhibited similar resistance but, compared with low-CI stands, high- and medium-CI stands had significantly lower recovery, resilience, and relative resilience, indicating they were more susceptible to drought stresses. Modeled CI was significantly negatively related to resistance, resilience, and relative resilience, indicating a density-dependence of tree response to drought. After exposure to multiple sequential drought events, the relative resilience of high-CI stands decreased to almost zero; this failure to fully recover to pre-drought growth rates suggests increased mortality in future. In contrast, low-CI stands are more likely to survive in hotter, more arid climates. These results provide a better understanding of the roles of competition and climate on the growth of Mongolian pines and offer a new perspective for investigating the density-dependent recovery and resilience of these forests.